Rural Healthcare - Cox, Jim (Taylor & Francis Group, 2023)
Rural Healthcare was the first textbook of rural medicine in the UK. In this fully revised second edition it continues to fulfil the requirement for a resource dedicated to the particular needs of those living and practising in rural areas
Description based on publisher supplied metadata and other sources
Keywords: Rural health services; Medicine, Rural